Formation of competition in the markets of the primary real estate: theoretical prerequisites, models, factors - Bielienkova, О. Yu.; Titok, V. V. (Ways to Improve Construction Efficiency, 2020)
The theoretical approaches to the assessment of competition in the Ukrainian markets are reviewed. The necessity to analyze the interconnection of components that describe competition in the market - structure, accessibility of housing, institutional development and business activity on the example of primary housing markets of Ukrainian regions, as well as the need to develop models of influence of these factors on the structure of markets and accessibility of housing for the population as basic characteristics for competitive construction company strategies. From the structural point of view, the primary real estate market of the regions of Ukraine is analyzed according to the CR-3 and Herfindahl-Hirschman concentration indices. It is revealed that the markets of the Kiev region. and Kiev are the least concentrated, the share of the three largest developers is 20-28%, which confirms the existence of competition in the housing sector of the city and the region. The markets of Kirovograd and Cherkasy regions were the most concentrated. The share of the three largest companies is 97-99%. By means of correlation-regression analysis, the equation of influence of factors characterizing institutional development, business activity and availability of housing on the market structure was created. The values of the factors that characterize the business activity of construction (number of enterprises and total area of residential buildings put into operation) and institutional development (introduction of the old-age institute, number of support funds for entrepreneurship) are inversely related to market concentration. The “affordable housing” and “united communities” factors are directly related to the result. That is, the larger the proportion of united territorial communities and the value of the accessibility factor, the more concentrated the residential real estate market. The model of influence on housing availability of the following factors was created: concentration coefficient, gross regional product per person, share of united communities in their total planned number, introduction of the Institute of Old Age, number of business centers, business support funds, coordination councils, number of business incubators , sq.m. non-residential buildings, commissioned per person.